Manj znane reliefne oblike v stenah Kraškega roba - Grmovšek, Andrej (Geografski obzornik, 2002)
In the faces of Kraški rob many landforms occur which are mainly typical of karst caves, bare karst and non-karstic faces. Described are some less known landforms, such as calcite-sedimentation results, i.e., ribs, needle-like speleothems and clod formations, and solution results, i.e. rainpits (floor pits), biopits, eyes and subsoil tubes. Their appearance, size, occurrence area and frequency are described and some hypotheses on their origin are presented.
Keywords: korozija; kraške oblike; kraški pojavi; Kraški rob; Primorska; Slovenija